Prosthetic rehabilitation of oligodontia in a child: a case report - Ahmed, Rubaba; Rayhanb, Md Ashik; Khan, Atiquzzaman; Rahman, Md Masudur (Update Dental College Journal, 2014)
Oligodontia is a developmental dental anomaly. It is either an isolated trait or part of a syndrome. Oligodontia is characterized by the congenital absence of more than six permanent teeth except the third molars. In this presented case, the treatment plan aimed at psychological, esthetic and functional rehabilitation of the patient who was suffering from oligodontia. After taking a thorough medical and dental history, clinical and radiological examination, the patient was treated with a removable partial denture in the maxillary arch, while a complete denture was made in the mandibular arch. The patients esthetics was greatly improved and early functional rehabilitation of the patient was done. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21167 Update Dent. Coll. j: 2014; 4 (1): 38-43